Adhesion to neuropathic pain treatment - Cardoso,Mirlane Guimarães de Melo (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: In recent decades the concept of adherence is evolving from one-dimensional approach, limited to following a medication regimen, to the understanding of factors involved in the success or failure of a treatment. In particular, neuropathic pain is characterized by treatment failure associated with high costs. In a recent literature review, non compliance rate with prescriptions for chronic pain ranged from 8 to 62%, and especially for neuropathic pain, the rate was 18%. The objective of this study was to investigate in Pubmed/Medline and Scielo databases publications regarding adherence to neuropathic pain treatment in the last ten years. CONTENTS: Descriptors used were: adherence, pain, neuropathic pain and compliance pain. It can be seen that in most studies (46 articles found in Pubmed and 49 in Scielo) adherence was examined with emphasis on adverse effects or efficacy associated with the use of drugs, or comparing the effects of two medications. Furthermore, 17 articles at Pubmed and 13 articles at Scielo focused on compliance of professionals with guidelines proposed by guideline entities. CONCLUSION: There are a few publications on adherence to neuropathic pain treatment. In general, most researches in this area deal with the effectiveness of medications. Few studies investigate the participation of psychosocial aspects in the adherence process. Given these findings we concluded that it is necessary to produce more knowledge related to this topic, expanding the understanding of this phenomenon considering biopsychosocial aspects.